MAX WEBER E OS DESCAMINHOS DA MODERNIDADE TÉCNICA - de Carvalho Leal, Edilene Maria (Prometheus - Journal of Philosophy., 2020)
This paper investigates some ambiguities present in Max Weber's conception of modernity, especially concerning the centrality of reason as an analytical category and as a model of social practices. For this, the arguments of the text have as their starting point aconstructionist conception of modernity which argues that the sociological and philosophical theories of modernity are self-descriptions that modern thinkers have made of modernity. The discussion is also supported by the presupposition that the Weberian conception of modern rationalization is due to a certain excess of positivation of rationality over irrationality.